Characterization of Three Fusarium graminearum Effectors and Their Roles During Fusarium Head Blight - Hao, Guixia; McCormick, Susan; Usgaard, Thomas; Tiley, Helene; Vaughan, Martha M. (Frontiers in Plant Science, 2020)
Fusarium graminearum causes Fusarium head blight (FHB) on wheat, barley, and other grains. During infection, F. graminearum produces deoxynivalenol (DON), which contaminates grain and functions as a virulence factor to promote FHB spread throughout the wheat head. F. graminearum secretes hundreds of putative effectors, which can interfere with plant immunity to promote disease development. However, the function of most of these putative effectors remains unknown. In this study, we investigated the expression profiles of 23 F. graminearum effector-coding genes during the early stage of wheat head infection. Gene expression analyses revealed that three effectors, FGSG_01831, FGSG_03599, and FGSG_12160, were highly induced by 272, 170, and 4300-fold respectively. We generated deletion mutants for these effector genes and performed FHB virulence assays on wheat head using point and dip inoculations to evaluate FHB spread and initial infection. No statistically significant difference in FHB spread was observed in the deletion mutants, ∆01831, ∆03599, and ∆12160. However, deletion mutants ∆01831 displayed a significant reduction in initial infection on wheat, and thus resulted in less DON contamination. To investigate their potential functions, these three effectors were transiently expressed in Nicotiana benthamiana leaves. N. benthamiana leaves expressing these individual effectors had significantly reduced production of reactive oxygen species (ROS) induced by chitin, but not by flg22. Furthermore, FGSG_01831 and FGSG_03599 markedly suppressed Bax-induced cell death when co-expressed with Bax in N. benthamiana leaves. Our study provides new insights into the functions of these effectors and suggests they play collective or redundant roles that likely ensure the successful plant infection.